A Review of Thermal Environmental Quality in Residential Areas in Tropical Cities. (May 2018) - Triyuly, Wienty; Triyadi, Sugeng; Wonorahardjo, Surjamanto
Abstract: The development of residential areas in big cities is characterized by a vertical-horizontal growth in the center of the city and horizontal growth in the edge of the city. The growth of the city has changed Land Use and Land Cover (LULC) and significantly altered the thermal environmental quality and urban heat island (UHI). This paper discusses the effects of the change LULC in several cities to their thermal environmental quality due to the development of residential area. We compare the effects of the change of LULC that occurred in residential areas in tropical cities. This study involves some factors such as the character building of residential, land cover, sun, and wind orientation. The results of this study present a map of various issues on the change of LULC in residential areas in tropical cities.